Impact of Luxurious Lifestyle Portrayals in Pakistani Dramas on Youth: A Study of Life Satisfaction and Dissatisfaction - Jilani, Sana; Khan, Farkhanda Shahid; Ali, Mah Rukh (Annals of Human and Social Sciences, 2024)
This research broadly deals with the depiction of glamour in Pakistani dramas and its effect on the contemporary youth. The study employs descriptive and quantitative research methods. The descriptive method analyzes TV dramas, while the quantitative method involves a questionnaire with ten questions designed to assess the impressions of luxurious lifestyle depicted in Pakistani dramas on youth. The questionnaire is adapted from a sample technique presented in William E. Glassman and Marilyn Hadad’s book Approaches to Psychology. This study contends that Pakistani television dramas face criticism for excessive glamorization, leading the audience into psychological conflicts. This study is significant since it explores the role of Television in shaping and altering attitudes of youth, and concludes that, the select TV dramas potentially disrupt the behavior of young adults. It recommends that these TV dramas can further be analysed under cultural Marxism and identity formation in Postmodernism.